MUHAMMADIYAH COUNCIL OF SOCIAL WELFARE DEVELOPMENT (MPKS) AND NATIONAL CHILD WELFARE POLICIES VIEWED THROUGH QAWA'ID FIQHIYYAH - Farhan Alif Ujilast; Aria Roby Putra (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
This article is a legal philosophy study, specifically examining the child welfare policies formulated by the Muhammadiyah Central Leadership. As a modernist Islamic movement, Muhammadiyah does not only prioritize religious texts (na?) in determining its policies. National laws in force in Indonesia also serve as empirical factors in seeking scientific truth. This study applies a literature study approach to examine the relationship between organizational policies (living law) and state law (civil law), in order to address child welfare issues through the philosophical foundations of Islamic law. Primary data were obtained from the 2021 Muhammadiyah Central Leadership Guidelines on Muhammadiyah's Social Service Enterprises and Law Number 35 of 2014 concerning Child Protection in its epistemological application. The elaboration of Islamic legal philosophy utilizes the epistemological function of qaw?'id fiqhiyyah studies, derived from Muhammad 'Abid Al-Jabir? work, Takwin al-'Aql al-'Arab?. The study reveals that Muhammadiyah's policies have a harmonious relationship with national laws related to the priority of child care within the family. This article proves epistemologically that qaw?'id fiqhiyyah functions to understand the application of law based on the development of religious texts.